The theory of centralized aerobic-anaerobic energy balance compensation and the right posture - Kirill V Zhukov; Bagrat A Gasparyan; Alexandre A Vetcher; Alexander Y Shishonin (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2022)
For over four centuries the posture was under very different points of view. The theory of centralized Aerobic-Anaerobic Energy Balance Compensation (CAAEBC) gives an additional angle of consideration, associated with the concept of brachiocephalic arterial blood flow access to the rhomboid fossa. This helps to understand the requirements of the set of physical exercises, that will be able to keep the posture training simultaneously with the healthcare.